Genome-Wide Search for Tyrosine Phosphatases in the Human Genome Through Computational Approaches Leads to the Discovery of Few New Domain Architectures. (April 2019) - Bhattacharyya, Teerna; Sowdhamini, Ramanathan
Reversible phosphorylation maintained by protein kinases and phosphatases is an integral part of intracellular signalling, and phosphorylation on tyrosine is extensively utilised in higher eukaryotes. Tyrosine phosphatases are enzymes that not only scavenge phosphotyrosine but are also involved in wide range of signalling pathways. As a result, mutations in these enzymes have been implicated in the pathogenesis of several diseases like cancer, autoimmune disorders, and muscle-related diseases. The genes that harbour phosphatase domain also display diversity in co-existing domains suggesting the recruitment of the catalytic machinery in diverse pathways. We have examined the current draft of the human genome, using a combination of 3 sequence search methods and validations, and identified 101 genes encoding tyrosine phosphatase-containing gene products, agreeing with previous reports. Such gene products adopt 37 unique domain architectures (DAs), including few new ones and harbouring few co-existing domains that have not been reported before. This semi-automated computational approach for detection of gene products belonging to a particular superfamily can now be easily applied at whole genome level on other mammalian genomes and for other protein domains as well.